Dynamics of Language Use in Socio-Academic Contexts and Their Implications for Language Teaching - Kholiq, Muh (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study explores the patterns of language use in the socio-academic context at Gunadarma University and their implications for language teaching. Using a qualitative descriptive approach with a case study design, this research examines translanguaging and code-switching as linguistic strategies in academic settings. The subjects are lecturers and students, while the object is bilingual communication in oral and written discourse. Data were collected through participatory observation of classroom interactions and in-depth interviews with lecturers and students. The collected data were analyzed using thematic analysis to identify key patterns and functions of language adaptation. Findings reveal that code-switching and translanguaging help clarify technical terms, overcome language barriers, and encourage student participation. Indonesian dominates internal communication and official documents, whereas English is preferred for academic and international contexts. Bilingual lecture notes and assignments enhance students' comprehension and bilingual proficiency. These findings emphasize the role of linguistic adaptation in fostering inclusivity in higher education. The study recommends bilingual language policies and lecturer training on code-switching techniques to improve teaching effectiveness. This research provides insights into pedagogical strategies that address students' linguistic needs in a dynamic academic environment.